Synthesis of hierarchical Mn2O3 microspheres for photocatalytic hydrogen production. (December 2016) - Li, Feng; Wangyang, Peihua; Zada, Amir; Humayun, Muhammad; Wang, Binsong; Qu, Yang
Graphical abstract: Highlights: Hierarchical Mn2 O3 microspheres with porous nanosheets were prepared. The self-assemble process of the microspheres was studied. The band structure of Mn2 O3 microspheres is confirmed. The hierarchical Mn2 O3 microspheres displayed enhanced photocatalytic H2 production activity. Abstract: Hierarchical Mn2 O3 microspheres have been prepared via polyol-mediated solvothermal method. The as-prepared hierarchical microspheres is about 8–10 μm in diameter assembled with porous nanosheets which favors charge transport. The formation process has been studied which is to form nanosheet first and then to self-assemble and finally to grow spheres. The band structure of Mn2 O3 microspheres is confirmed through XPS valence spectrum and UV-vis, verfiying that it is suitable for hydrogen reduction. The H2 production efficiency of hierarchical Mn2 O3 microspheres is found to three time higher than that of Mn2 O3 particles. The promoted photocatalytic hydrogen production efficiency could be attributed to the interesting hierarchical structure, large surface area and suitable band gap.